100TH ANNIVERSARY OF THE SOVIET MATERNAL AND CHILD HEALTHCARE SYSTEM: SUCCESSES, PROBLEMS, AND LESSONS - Alexander A. Baranov; Valery Yu. Albitsky (Вопросы современной педиатрии)
The article presents the text of the authors' report at the plenary session of the XX Congress of Pediatricians of Russia (dated February 16, 2018) dedicated to the centenary of the Soviet state mother and child welfare system. The features of its formation and development were described. The most important achievements in the field of child health care were outlined. Attention is focused on the personalities of the first facilitators of pediatric healthcare in Soviet Russia. Authors summarise the findings resulting from the history of the Soviet pediatric service.